2002
DOI: 10.1074/jbc.m200316200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Guanine-derived Formamidopyrimidine Lesion on DNA Replication

Abstract: 2,6-Diamino-4-hydroxy-5-formamidopyrimidine derived from guanine (FapyG) is a major DNA lesion formed by reactive oxygen species. In this study, a defined oligonucleotide template containing a 5-N-methylated analog of FapyG (mFapyG) was prepared, and its effect on DNA replication was quantitatively assessed in vitro. The results were further compared with those obtained for 7,8-dihydro-8-oxoguanine and an apurinic/ apyrimidinic site embedded in the same sequence context. mFapyG constituted a fairly strong but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 59 publications
2
29
1
Order By: Relevance
“…Replication across these lesions by DNA polymerases results in the misincorporation of nucleotides and the establishment of mutations in daughter chromosomes [1][2][3][4][5]. The synthesis of oligonucleotides containing chemically defined bases permits the study of translesion synthesis and consequent misincorporation by a number of DNA polymerases [6][7][8][9][10][11][12][13][14][15][16]. 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) can assume either a syn or anti-orientation depending on its base pairing partner [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Replication across these lesions by DNA polymerases results in the misincorporation of nucleotides and the establishment of mutations in daughter chromosomes [1][2][3][4][5]. The synthesis of oligonucleotides containing chemically defined bases permits the study of translesion synthesis and consequent misincorporation by a number of DNA polymerases [6][7][8][9][10][11][12][13][14][15][16]. 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) can assume either a syn or anti-orientation depending on its base pairing partner [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…When nucleotides are presented individually, these two enzymes insert dTMP and to a lesser extent dGMP which demonstrates that 8-oxodA has limited mutagenic potential [12]. The Klenow fragment and DNA polymerase α preferentially insert dAMP opposite both synthetic and natural abasic sites [14][15][16]. Abasic sites also promote sequence-dependent 1 and 2 bp deletions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using the methylated analogue of FapyG, i.e. 2,6-diamino-4-hydroxy-5-Nmethylformamidopyrimidine (Me-FapyG), have suggested that formamidopyrimidines might also constitute blocks to DNA polymerases (10,11). It is noteworthy, however, that FapyG and FapyA are chemically distinct from Me-FapyG.…”
mentioning
confidence: 99%
“…We first prepared four 30-base paired oligodeoxynucleotides containing CG ϫ CG, mCG ϫ mCG, mCG ϫ mCmG, or CG ϫ CmG in a unique position by using a primer extension reaction as described (Fig. 5A) (40,41). An electrophoretic mobility-shift assay was performed by using these double-stranded DNAs and bacterially expressed MBD of MBD1 (Fig.…”
Section: Molecular Dynamics Of Mbd1 and Mpg Under Mms-induced Dnamentioning
confidence: 99%